Clinical and radiological factors affecting progression in sarcoidosis - Aycicek, Olcay; Emiroglu, Ensar Cihat; Coban, Kadir; Erbay, Muge; Ozlu, Tevfik; Oztuna, Funda; Bulbul, Yılmaz (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: To determine the clinical and radiological indicators of disease progression in a newly diagnosed sarcoidosis patient.Methods: The data of patients who were diagnosed with sarcoidosis in our department between January 2014 and June 2022 were analyzed. The patients were divided into two groups: progression and non-progression.Groups were compared according to symptoms at the time of diagnosis, comorbidities, foci of extrapulmonary involvement, shape, size, density, and localization of mediastinal lymph nodes, parenchymal findings, disease stage  and whether or not treatment was received at the beginning.Results: The study included 292 sarcoidosis patients. The number of patients who progressed was 46 (15.8%). It was observed that stage II patients progressed more than stage I patients (p